Case Series of Anthrax in Iran - Kiana Shirani; Zahra Senemar; Reza Fadaei Nobari; Parisa Ataabadi (Clinical Case Reports)
ABSTRACT In endemic areas with a compatible epidemiological context, clinicians should consider anthrax as a potential diagnosis. The disease can present with diverse clinical manifestations, including cutaneous, gastrointestinal, respiratory, or central nervous system infections.